Fine needle aspiration cytology of thyroid and its correlation with serological findings - Karki, S; Shrestha, A (Journal of Pathology of Nepal, 2017)
Background: Thyroid autoimmunity can cause several forms of thyroid disorders i.e. Grave’s disease, Hashimoto’s thyroiditis, atrophic autoimmune thyroiditis, post-partum thyroidits etc. Cytological diagnosis may be sometimes difficult is some cases. In such conditions, cytology along with serological tests aid at reaching a correct diagnosis.Hence, this study was undertaken to evaluate the serum level of anti-TPO antibody with respect to serum concentrations of thyroid hormones and its importance in diagnosing autoimmune thyroiditis. Material and Methods: This study was carried out in the department of pathology from June 2013-May 2014. Patients coming to the department of pathology TUTH, Maharajgunj for FNA of thyroid were included. TFT level was noted and anti TPO antibody level was evaluated by CLIA. Results: Ninety-five thyroid FNAC was included in the study, which comprises of 16.8 % males and 83.2% females with a M: F 1: 4.9. Maximum number of cases was seen in the age range 21-30 years (25.3%), mean age being 40.4years. The cytological diagnosis comprised colloid goiter(43.2%), lymphocytic thyroiditis (25.3%), Hashimoto thyroiditis(18.9%). Out of 42 cases of autoimmune thyroiditis diagnosed cytologically, 16 (38%) were hypothyroid, 4 (9.5%) hyperthyroid, 8 (19%) sub-clinical hypothyroid and 14 (33.5%) were euthyroid. The sensitivity and specificity of positive anti TPO in correctly identifying autoimmune thyroiditis was 85.7% and 79.2% respectively. The positive and negative predictive value for the test was 76.5% and 87.5% respectively. Conclusion: Nodular goitre can harbour a certain per cent of autoimmune thyroiditis and in such cases anti TPO antibody level along with cytodiagnosis appears to be helpful.